Plastic-film mulch improves Vicia unijuga seed yield and yield components under subalpine climate conditions. Issue 9 (28th July 2020) - Tang, Wei; Coulter, Jeffrey A.; Hu, Xiao-Wen; Han, Yun-Hua; Wang, Yan-Rong; Zhang, Zhi-Xin; Li, Rui; Nan, Zhi-Biao
ABSTRACT: Perennial vetch ( Vicia unijuga A. Br.) is a valuable protein-rich forage crop to develop grassland animal husbandry in subalpine regions of the Qinghai-Tibetan Plateau. Unsatisfied seed yield (SY) is often a setback constrained by the cold and erratic precipitation environments. Techniques based on mulching (e.g. plastic-film and straw) efficiently improve SY of crops, but little is known about SY response of V. unijuga to mulching. A 3-year field experiment was conducted in a subalpine region of China to evaluate the effects of three mulching treatments – plastic-film mulching (FM), removal of plastic-film mulching at the 30% flowering stage (RM) and barley straw mulching (SM) – on SY and yield components of V. unijuga . Higher soil temperature and water contents were recorded in the FM treatment than in Control and other treatments. The greatest SY was achieved in the FM treatment, with a mean SY of 72.3 g m -2 for the 3 years. Among the yield components, inflorescences m -2 had the highest direct impact on SY, and explained 42.0% of the variation in SY. In conclusion, in subalpine regions, the FM treatment is an effective mulching method for enhancing SY of V. unijuga, and the response arises primarily through increasing initial inflorescence density. Abbreviations: FI: florets per inflorescence; IS: inflorescences per square meter; LAI: leaf area index; OF: ovules per floret; PI: pods per inflorescence; SB: shoot biomass; SP: seeds per pod; ST: soil temperature; SWC: soil water content; SY: seed yield; PSY: potential seed yield; TSW: thousand seed weight; Control: non-mulched control; FM: plastic-film mulch for the entire season; RM: plastic-film mulch cover until 30% flowering; SM: naked barley ( Hordeum vulgare L. var. nudum Hook. f.) straw mulch for the entire season; FFS: full flowering stage; IFS: initial flowering stage; MS: maturity stage; PFS: pod-filling stage